DAMPAK CURAH HUJAN, SUHU DAN KELEMBABAN PADA PERTUMBUHAN TEBU (SACCHARUM OFFICINARUM L.) VARIETAS BULULAWANG - Faiq Fadlulloh Subqi; Anna Kusumawati; Lintang Panjali Siwi Pambayun (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2026)
Sugarcane growth and yield are influenced by the interaction between plant factors, soil conditions, climate, and cultivation practices. Climate is an uncontrollable component, so it is an important aspect that must be carefully considered in sugarcane cultivation activities. Three important variables are rainfall, humidity, and temperature, and to date, research related to the relationship between climate variables and sugarcane growth has not been widely conducted. This study aims to determine the relationship between sugarcane growth and climate conditions (rainfall, humidity, and air temperature). This study used three locations: Magelang, Purworejo, and Kulon Progo, in sugarcane areas with the Bululawang variety and plant age. The observed plant growth variables included stem height, stem diameter, number of leaves, number of stems per clump, and number of sugarcane internodes in each field. Meanwhile, the observed climate variables were rainfall, temperature, and humidity (obtained from BMKG). Data analysis was carried out using descriptive quantitative data and a person correlation test using Excel. The results showed that Magelang had the highest rainfall and Kulon Progo had the lowest rainfall. The air temperature in Purworejo was the highest and Kulon Progo had the lowest. The highest humidity is in Purworejo and the lowest humidity is in Magelang. Rainfall has a significant correlation with sugarcane growth, while temperature and humidity have a correlation but are not significant. Rainfall has a very strong and significant correlation with stem diameter (r = -0.835), number of internodes (r = -0.857), and number of stems per clump (r = -0.897). Air temperature and air humidity have a very low and insignificant correlation with all plant growth variables. This indicates that rainfall is the most important climate factor influencing sugarcane growth.